CTM264 : Theatre management and organisation / College of Creative Arts - UiTM, College of Creative Arts
Students will apply all aspect of theatre organization including the responsibilities and job requirements in a production structure of management, artistic and technical. All applications are carried out in paperwork and real time practice assignments.